2023
DOI: 10.1177/21501351221127895
|View full text |Cite
|
Sign up to set email alerts
|

How do Adults With Congenital Heart Disease Evaluate Their Clinical Care?

Abstract: Background Almost 90% of patients with congenital heart disease (CHD) now reach adulthood. How do they evaluate the care they received? Methods Adults with CHD (ACHD) recruited for an international multi-center study (APPROACH-IS II) were posed 3 additional “questions” to determine their perceptions of the positive, negative, and areas for improvement of their clinical care. The findings underwent a thematic analysis. Results Of the 210 recruited, 183 completed the questionnaire, 147 answered the 3 “questions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Nevertheless, many young ACHD patients still have an expectation that their ongoing care should not cost them anything. 36,39…”
Section: Results and Commentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, many young ACHD patients still have an expectation that their ongoing care should not cost them anything. 36,39…”
Section: Results and Commentsmentioning
confidence: 99%
“…14,40,41 Outreach ACHD services have been set up in New South Wales and Victoria in Australia. 39 Lammers et al reported the existence of a cluster of “time sensitive patients” who tended to be younger and with less serious CHD, who were more likely to rate factors such as shorter drive, wait times for an appointment, the ambience of the consulting rooms, and the punctuality of the attending clinician as important aspects to influence their ongoing involvement. 21 In contrast, those with more complex CHD tended to seek out more knowledgeable and experienced clinicians.…”
Section: Results and Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 Remote consultation improves access for those living further away, having difficulty with transport or experiencing anxiety attending hospital. 25 These options and others could surpass the traditional clinic system in parallel with individualised surveillance pathways for anticipated medical complications.…”
Section: Discussionmentioning
confidence: 99%